Exploring divergences in comparative research: citizenship regimes and the spectacular cities of Central Asia and the GCC. Issue 4 (7th July 2015) - Koch, Natalie
Abstract : Interrogating the concept of 'legality' and how it relates to local citizenship regimes, this article shows how a focus on cross‐regional divergences can offer theoretical insights into the political implications of projects that, on the surface, appear to be strikingly similar. Taking the case of apparently similar spectacular capital city development schemes in the resource‐rich states of Central Asia and the Gulf Cooperation Council (GCC), I show that there are significant differences in the underlying political geographic and political economic factors that makes them possible, as well as the political relations they sustain and produce. Like most states around the world, foreigners represent a minority of the overall population of the Central Asian states, but in the GCC, citizens are in the minority of the population in most countries. Because of this political configuration, the capital city development schemes are broadly coded as legal and legitimate in the Gulf, but illegal and corrupt in Central Asia. By honing in on these two different regions, this study shows how the state's power to define citizenship, and thus who is entitled to its resources, is a tremendously powerful technology of government, which hinges on actively constructing a binary between the 'legal' and 'illegal'.